Efektivitas Dan Strategi Komunikasi Antarbudaya Dalam Membangun Keharmonisan Sosial Serta Adaptasi Individu Di Era Globalisasi - Hasriyodan Hasriyodan; Arifuddin Tike; Sattu Alang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Intercultural communication is a crucial element in maintaining social harmony within plural and multicultural societies such as Indonesia. In the context of globalization, where human mobility and cross-border information exchange are increasingly intense, the ability to communicate effectively across cultures has become an urgent necessity. This study aims to examine the effectiveness and strategies of intercultural communication in fostering social harmony, as well as to describe the forms of communication adaptation undertaken by individuals in facing cultural differences. Using a literature review method and a descriptive qualitative approach, this study finds that intercultural communication that is open, empathetic, and responsive to differences in values and social norms can enhance tolerance, reduce conflict, and strengthen social cohesion. Moreover, communication strategies through both macro (mass media) and micro (direct interaction) approaches are proven to be effective in building intercultural relationships. Individual communication adaptation, such as language learning and adjusting communication styles, plays a key role in addressing cross-cultural challenges in the era of globalization. Therefore, strengthening intercultural communication competence is a fundamental step in building an inclusive, peaceful, and harmonious society.